2017
DOI: 10.3390/en10040550
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Charging and Discharging Scheduling for Electric Vehicles in a Parking Station with Photovoltaic System and Energy Storage System

Abstract: Abstract:The economic and environmental benefits brought by electric vehicles (EVs) cannot be fully delivered unless these vehicles are fully or partially charged by renewable energy sources (RES) such as photovoltaic system (PVS). Nevertheless, the EV charging management problem of a parking station integrated with RES is challenging due to the uncertain nature of local RES generation. This paper aims to address these difficulties by deploying an energy storage system (ESS) in parking stations and exploiting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(44 citation statements)
references
References 46 publications
0
40
0
Order By: Relevance
“…References [20][21][22] focus on V2G without PV. Reference [23] ignores battery degradations costs, and [20] has an unrealistically small and unjustified figure of 1 ¢/kWh. References [24,25] only use EV batteries to cover the difference between forecasted and actual PV generation, without exploiting the batteries for storing the surplus generation and thus underusing the capacities of the batteries.…”
Section: Related Research In Electric Vehicle Battery Exploitationmentioning
confidence: 99%
See 1 more Smart Citation
“…References [20][21][22] focus on V2G without PV. Reference [23] ignores battery degradations costs, and [20] has an unrealistically small and unjustified figure of 1 ¢/kWh. References [24,25] only use EV batteries to cover the difference between forecasted and actual PV generation, without exploiting the batteries for storing the surplus generation and thus underusing the capacities of the batteries.…”
Section: Related Research In Electric Vehicle Battery Exploitationmentioning
confidence: 99%
“…References [24,25] do not consider the fact that each vehicle has individual state of charge (SOC), departure time and intended minimum SOC level on departure. Reference [23] requires investment to local energy storage in addition to the EV batteries, but this cost is not discussed. The listed approaches cannot be directly quantitatively compared to our proposal due to the issues, which can be classified into one of the following categories:…”
Section: Related Research In Electric Vehicle Battery Exploitationmentioning
confidence: 99%
“…Other than the optimization methods, there also exist various kinds of optimization objectives, such as the minimization of charging cost, minimization of grid load variance, maximization of aggregators' profit, maximization of average state-of-charge of vehicles, and many others. A summary on the optimization objectives can be found in [31]. Nevertheless, for the above studies, there still exist the problems below.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of EVs on the power grid is a commonly faced problem [10][11][12][13][14]. An increase in the EV diffusion can cause new peak loads in the power generating system and problems with the power dispatch and quality.…”
mentioning
confidence: 99%
“…An interesting review can be found in [27,28]. It is obvious that difficulties arise to the intermittent nature of the photovoltaic and wind sources, and this problem is faced in [14]. From all these aspects, it is evident that there is still no certainty to face the next demands of energy by increasingly growing fleets of EVs.…”
mentioning
confidence: 99%